Efficacy and Safety of Rebamipide versus Its New Formulation, AD-203, in Patients with Erosive Gastritis: A Randomized, Double-Blind, Active Control, Noninferiority, Multicenter, Phase 3 Study - Kim, Gwang Ha; Lee, Hang Lak; Joo, Moon Kyung; Park, Hong Jun; Jung, Sung Woo; Lee, Ok-Jae; Kim, Hyungkil; Chun, Hoon Jai; Lee, Soo Teik; Kim, Ji Won; Jeon, Han Ho; Chung, Il-Kwun; et al. (Gut and liver, 2021)
: The mucoprotective drug rebamipide is used to treat gastritis and peptic ulcers. We compared the efficacy of Mucosta (rebamipide 100 mg) and its new formulation, AD-203 (rebamipide 150 mg), in treating erosive gastritis. This double-blind, active control, noninferiority, multicenter, phase 3 clinical trial randomly assigned 475 patients with endoscopically proven erosive gastritis to two groups: AD-203 twice daily or Mucosta thrice daily for 2 weeks. The intention-to-treat (ITT) analysis included 454 patients (AD-203, n=229; Mucosta , n=225), and the per-protocol (PP) analysis included 439 patients (AD-203, n=224; Mucosta , n=215). The posttreatment assessments included the primary (erosion improvement rate) and secondary endpoints (erosion and edema cure rates; improvement rates of redness, hemorrhage, and gastrointestinal symptoms). Drug-related adverse events were evaluated. According to the ITT analysis, the erosion improvement rates (posttreatment) in AD-203-treated and Mucosta -treated patients were 39.7% and 43.8%, respectively. According to the PP analysis, the erosion improvement rates (posttreatment) in AD-203-treated and Mucosta -treated patients were 39.3% and 43.7%, respectively. The one-sided 97.5% lower limit for the improvement rate difference between the study groups was -4.01% (95% confidence interval [CI], -13.09% to 5.06%) in the ITT analysis and -4.44% (95% CI, -13.65% to 4.78%) in the PP analysis. The groups did not significantly differ in the secondary endpoints in either analysis. Twenty-four AD-203-treated and 20 Mucosta -treated patients reported adverse events but no serious adverse drug reactions; both groups presented similar adverse event rates. The new formulation of rebamipide 150 mg (AD-203) twice daily was not inferior to rebamipide 100 mg (Mucosta ) thrice daily. Both formulations showed a similar efficacy in treating erosive gastritis.